PESAN MORAL RELIGI DALAM PUISI MANDAR KALINDAQDAQ MASAALA: ANALISIS SEMANTIK - Widayati, Tri Lutfi; Masrukhi, Moh. (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Kalindaqdaq masaala poetry is one of the literary works in a variety of kalindaqdaq poetry themes that are still preserved in the Mandar land of West Sulawesi. In terms of language, kalindaqdaq poetry tends to be free, not bound by specific rules. The language used is Mandarese and the amount of figurative language makes it sometimes difficult for kalindaqdaq lovers to understand the meaning contained in the words used. understand the meaning contained in the words used. This research aims to describe the meaning contained in the poem by using semantic analysis that focuses on the meaning of the poem. using semantic analysis that focuses on lexical meaning, grammatical meaning, referential meaning, and figurative meaning. The research method used is the descriptive qualitative method. The results of the discussion show that this poem can be analyzed using semantic studies. This poem explains about moral messages, religion, advice, and religious orders as well as possible. Keywords: kalindaqdaq masaala, mandar poetry, semantic.